Advances in synthetic organic chemistry and methods reported in US patents - DeRosa, Thomas F. (Elsevier, 2006)
Advances in Synthetic Organic Chemistry and Methods Reported in US Patents provides synthetic guidelines for preparing current and commercially significant organic compounds, derivatives, and intermediates as reported in issued US Patents. Industries surveyed include agrochemical, cosmetics and personal care products. Each entry contains extensive information such as explicit laboratory directions for preparing all chemical intermediates and characterization data. Furthermore, product optimization studies, industrial preparation, and new synthetic methods have been included for selected entries, as well as projected research directions for future product development. In Advances in Synthetic Organic Chemistry and Methods Reported in US Patents the author's practical approach enables readers to identify research and market trends, and stay up-to-date on current developments in the field. * Provides synthetic guidelines for preparing current and commercially significant organic compounds, derivatives, and intermediates as reported in issued US Patents * Identifies product development trends to help determine research areas * Elucidates use of the US Patent and Trademark Office database.